2019
DOI: 10.1177/0894845319853879
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Overqualification, Boredom, and Extra-Role Behaviors: Testing a Moderated Mediation Model

Abstract: Despite increasing research on the mechanisms that underlie the relation between perceived overqualification (POQ) and extra-role behaviors, the relation’s affective mechanisms have been understudied. In this study, we focus on the role of job boredom among overqualified workers in order to understand two types of extra-role behaviors: counterproductive work behaviors (CWB) and organizational citizenship behaviors (OCB). Using a sample of white-collar employees in South Korea ( N = 298), we found that job bore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 64 publications
(145 reference statements)
1
30
0
1
Order By: Relevance
“…Otherwise, even if the use of smartphones is prohibited, employees will kill boredom in other ways (e.g., cyberloafing, doodling, and fidgeting). Given overqualified individuals are more likely to experience job boredom (Kim et al, 2021), organizations should select qualified employees rather than overqualified ones. For existing overqualified employees, the organization should assign them more challenging tasks (Kim et al, 2021) to improve their person-job fit and to decrease their job boredom.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Otherwise, even if the use of smartphones is prohibited, employees will kill boredom in other ways (e.g., cyberloafing, doodling, and fidgeting). Given overqualified individuals are more likely to experience job boredom (Kim et al, 2021), organizations should select qualified employees rather than overqualified ones. For existing overqualified employees, the organization should assign them more challenging tasks (Kim et al, 2021) to improve their person-job fit and to decrease their job boredom.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Given overqualified individuals are more likely to experience job boredom (Kim et al, 2021), organizations should select qualified employees rather than overqualified ones. For existing overqualified employees, the organization should assign them more challenging tasks (Kim et al, 2021) to improve their person-job fit and to decrease their job boredom. In addition, previous studies have shown that having more job resources could reduce the job boredom of employees (Harju et al, , 2018Toscanelli et al, 2021).…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 而招聘者也需承担员工入职后因对工作不满意而离 职的风险 (Maynard et al, 2006) 。 同 时 , 根 据 个 人 -环 境 匹 配 理 论 (person-environment fit, P-E fit theory)和角色理论 (role theory), 当员工感觉自身才干超出工作需要、 技能缺乏利用时 (Kim et al, 2019;Sánchez-Cardona et al, 2019), 或感觉所相处的上级、同事、客户等对 社会角色的扮演不符合自身期望的标准时 (Darden, 1999;Loukidou et al, 2010), 都会产生无聊的体验。 无聊表现为个体对工作缺乏兴趣, 难以集中注意力 (Fisher, 1993), 会促使个体采取行动去提升工作环 境的吸引力, 甚至不惜以冒险、越轨的形式来摆脱 无聊感 (Barbalet, 1999)。相较而言, 公平理论和相 对剥夺理论侧重于描述个体对自我与其他社会群体 的人际比较 (Crosby & Gonzalez-Intal, 1984), 个人− 环境匹配理论强调个体对自身素质、能力、条件等 与 所 处 组 织 、 岗 位 需 求 等 客 观 工 作 特 征 的 比 较 (Kristof, 1996), 角色理论则涉及社会生活中个人 将 社 会 互 动 现 状 与 自 身 期 望 标 准 的 比 较 (Darden, 1999;Loukidou et al, 2010) (Ma et al, 2020;van Dijk et al, 2019;Wang, 2019;Zhang et al, 2016 (Hofstede, 1980;Hofstede et al, 2010;Triandis, 1989 (Chen, 1995;Hui, 1988;Waterman, 1984 (Jasso, 1993), 个体既 有可能采取报复行为、反生产行为、离职等消极应 对模式 (Barclay et al, 2005;Fine & Nevo, 2008;Kim et al, 2019;Maynard & Parfyonova, 2013;Yang & Diefendorff, 2009), 也有可能通过工 作重塑、建言、创新等有益于组织的反应, 改善工 作现状, 规避不愉快的心理体验 (Lin et al, 2017;Zhou & George, 2001) (Chen, 1995;Hui, 1988;Jackson et al, 2006;Waterman, 1984) (Markus & Kitayama, 1991;Parkes et al, 1999) (Luksyte et al, 2020;…”
unclassified